Constitutional Court vs. Lawmakers: Positive Legislature, Decision Implementation, and Balance of Authority - Muttaqin, Labib; Enggarani, Nuria Siswi; Nurhayati, Nunik; Junaidi, M.; Febiyanti, Nabilla (SIGn Jurnal Hukum, 2025)
The Constitutional Court’s transition from a negative legislator to an executor of positive legislation has created structural tension with Lawmakers. This phenomenon creates legislative resistance that impedes decision implementation, often leaving constitutional compliance to rely on public pressure. This research aims to analyze the roots of such disharmony and to formulate a procedural law design capable of effectively guaranteeing the execution of decisions. Through a normative legal research method using the statute approach, conceptual approach, and case approach, this study examines constitutional dynamics following the Constitutional Court’s delivery of two decisions regarding the judicial review of Law Number 10 of 2016 and Law Number 11 of 2020. The research results indicate that implementation barriers stem from the counter-majoritarian difficulty and the obsolescence of Chapter V of Law Number 24 of 2003, which fails to accommodate the complexity of positive legislature authority. As an absolute solution, this research recommends the urgent formation of a stand-alone Constitutional Court Procedure Bill (separate bill). This Bill must grant the Constitutional Court attribution authority to establish a “mandatory deadline” (tenggat waktu eksekutorial) for Lawmakers. Formalizing this mechanism is crucial to restoring the balance of the separation of powers system and ensuring the enforcement of constitutional supremacy through an institutionalized mechanism with legal certainty.